2020
DOI: 10.1101/2020.01.30.916270
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The genetic structure and adaptation of Andean highlanders and Amazonian dwellers is influenced by the interplay between geography and culture

Abstract: Western South America was one of the worldwide cradles of civilization. The well known Inca Empire was the tip of the iceberg of a cultural and biological evolutionary process that started 14-11 thousand years ago. Genetic data from 18 Peruvian populations reveal that: (1) The between-population homogenization of the central-southern Andes and its differentiation with respect to Amazonian populations of similar latitudes do not extend northward. Instead, longitudinal gene flow between the northern coast of Per… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…The Mekong River running through southeastern Cambodia as well as the urbanized area of Phnom Penh, may both have contributed to reduced parasite migration in this part of Cambodia. The fact that detected migration hotspots and barriers were geographically related with landcover and hydrologic features underscores the role that geography plays in shaping parasite population structure, which is consistent with findings from other studies, for example, a major migration barrier was detected around the Andes Mountains in Peru [56].…”
Section: Discussionsupporting
confidence: 90%
“…The Mekong River running through southeastern Cambodia as well as the urbanized area of Phnom Penh, may both have contributed to reduced parasite migration in this part of Cambodia. The fact that detected migration hotspots and barriers were geographically related with landcover and hydrologic features underscores the role that geography plays in shaping parasite population structure, which is consistent with findings from other studies, for example, a major migration barrier was detected around the Andes Mountains in Peru [56].…”
Section: Discussionsupporting
confidence: 90%
“…From the genetics point of view, two recent independent studies [ 60 , 61 ] have identified east-west gene flow linking the north Peruvian coast and highlands with Amazonian groups to the east of the northern Andes. Interestingly, one of these studies has found gene flow between the Chachapoyas and populations from the Jivaroan ethnolinguistic stock such as the Awajún and Candoshi [ 61 ]. This evidence gives further support to our finding despite the lack of published historical works on ancient or recent migrations from Jivaroan populations towards the Chachapoya territory or vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…To infer the genetic ancestry for Brazilians, we used the three parental populations: 502 African and 503 European individuals from the 1000 Genomes Project phase-III ( 33 ), and 234 Native American individuals ( 34 ).…”
Section: Methodsmentioning
confidence: 99%